Sports culture and its relationship to sports identity among students at the College of Physical Education and Sports Sciences at Anbar University - Ali Khalaf, Yaseen (Cuestiones de Fisioterapia, 2024)
This study's objectives are to ascertain the degree of sports culture and identity among Anbar University students studying physical education and sports sciences, as well as the correlation between these two concepts and the contribution of sports satellite channels to the growth of sports culture among these students. A survey method was combined with a descriptive approach. For morning and evening studies, the research team comprised fourth-year Anbar University students studying physical education and sports sciences for the current academic year (2023-2024). The majority of the study sample was selected at random. There were 152 male and female pupils in total, with a proportion of 10.60% from the study population and 53.71% overall. The researcher came to the conclusion that Anbar University's sports science students had a very high degree of sports culture and sports identity after gathering, presenting, analyzing, and quantitatively discussing the data. Students' degree of sports culture influences their degree of sports identity, and vice versa. A greater proportion of students thought that satellite sports channel viewing contributed to the growth of sports culture.